Uninjured youth athlete performance on single-leg hop testing: How many can achieve recommended return-to-sport criterion? - Greenberg, E. M.; Dyke, J.; Leung, A.; Karl, M.; Lawrence, J. T.; Ganley, T. (Sports Health: A Multidisciplinary Approach, 2020)
Background: Current anterior cruciate ligament reconstruction (ACLR) guidelines utilize single-leg hop tests (SLHTs) to assist in return-to-sport decision making. A limb symmetry index (LSI) of =90% is often required; however, after ACLR, most youth athletes cannot achieve this standard. Reporting the performance of age-matched normative controls will allow clinicians to compare post-ACLR performance with noninjured peers, improving the utility of SLHTs. The purpose of this study was to report hop test LSI within healthy youth athletes and determine whether athlete performance surpasses post-ACLR requirements.